System-Level Design Principles for Trustworthy Artificial Intelligence (AI Governance and Society Journal p-ISSN 3117-6097 and e-ISSN 3117-6100, 2024)
Trustworthy artificial intelligence (TAI) demands that AI systems satisfy a constellation of system-level properties --safety, reliability, fairness, transparency, privacy, and human oversight -- in a coherent, verifiable, and maintainablemanner across their operational lifetime. This paper derives and empirically validates twelve System-Level DesignPrinciples (SLDPs) for TAI, organised under four architectural layers: data, model, integration, and governance. TheSLDPs are evaluated through a cross-sectional expert assessment involving 42 AI system architects from nine countriesand a longitudinal deployment study tracking 16 AI systems across healthcare, autonomous systems, and financialservices domains over 18 months. Expert consensus confirms strong agreement on principle importance (mean KendallW = 0.81, p < 0.001). Longitudinal analysis demonstrates that systems implementing eight or more SLDPs exhibit a47.2% lower rate of trust-critical incidents compared to systems implementing fewer than four (IRR = 0.53, 95% CI:0.41-0.68, p < 0.001). The study contributes a consolidated SLDP catalogue, a TAI System Maturity Index (TSMI), andpractical guidance for operationalising EU AI Act and NIST AI RMF requirements.